A survey of health status of healthcare providers in a square cabin hospital during the new corona omicron outbreak: A cross-sectional study - Pei, Haoyu; Gan, Xiaoqin; Guo, Fei; Wu, Qiuping; Liu, Ding; Li, Zhouzhou; Lan, Ping; Zhang, Lili; Yan, Hong (Frontiers in Psychology, 2022)
Background: The coronavirus omicron variant outbroke in early 2022 in Shanghai. Although previous studies indicated that long working hours in a square cabin hospital might increase the risk of mental health among frontline healthcare providers, few studies have investigated whether the mental health risk could be reduced among well-trained professionals following the new guidelines. Objective: This study aimed to investigate the health situation of frontline healthcare providers in Shanghai square cabin during the omicron variant circulation. Methods: An online survey was used to evaluate those healthcare providers working in the square cabin hospitals from March 1, 2022, to May 31, 2022. The first online survey was conducted and emailed to the health providers on April 1. The second survey was conducted and sent to the nonrespondents on May 31. Overall, 142 frontline healthcare providers completed the online survey. Their mental health was assessed by the Insomnia Severity Index Scale, the Generalized Anxiety Disorder Scale, the Patient Health Questionnaire-9, and the Psychological Resilience Scale. We estimated multiple clinical systems and identified factors associated with those symptoms among participants. Multivariable logistic regression models were used to assess the risk factors of these symptoms. Results: Overall, 66.20%, 45.07%, and 27.46% of frontline healthcare providers in Shanghai City reported symptoms of insomnia, depression, and anxiety, respectively. In addition, the most common symptoms included dry eyes (57.75%), lumbar muscle strain (47.18%), dry mouth (35.92%), itching (31.69%), headache (29.58%), and sore throat (28.87%) among the frontline healthcare providers. There was no statistical difference in symptoms by gender, age, personnel category, or job position (P>0.05). Conclusion: In the case of an unexpected pandemic, the mental health of healthcare providers is not optimistic. This situation still exists more than two years after the global outbreak of the COVID-19 pandemic. Therefore, the physical and mental health of long-term healthcare providers working in a square cabin hospital still needs monitoring.